SPE California Regional Meeting 1987
DOI: 10.2118/16375-ms
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Effects of an Oil Phase on the Propagation of Foam in Porous Media

Abstract: Laboratory experiments were performed to determine the effects of a residual oil phase to hot nitrogen flood an the propagation of surfactant foam in Berea sandstone rocks. Static phase behavior-type tests were performed in support of the displacement tests. In the static experiments, surfactant partitioning into the oil phase and thermal degradation losses were measured. The chemical and physical properties of the oil phase were varied by the employment of four crude oil and two synthetic oil samples. The che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Their results show that foam performance is strongly sensitive to surfactant type, but not affected as strongly by oil type. Similar results were also obtained in Jensen and Friedmann's study [17]. They indicated that the influence of oil on foam largely depends on surfactant type.…”
Section: Introductionsupporting
confidence: 87%
“…Their results show that foam performance is strongly sensitive to surfactant type, but not affected as strongly by oil type. Similar results were also obtained in Jensen and Friedmann's study [17]. They indicated that the influence of oil on foam largely depends on surfactant type.…”
Section: Introductionsupporting
confidence: 87%
“…For the strongly water-wet case, foam was observed at the outlet after a 4-PV delay, whereas foam was not observed at the outlet for the oil-wet cases (104-410 PV injected) (i.e., foam collapsed or changed its confi guration when advancing through the fractures). The destabilization of foam inhibits further foam-front movement (Bernard and Jacobs 1965;Jensen and Friedmann 1987). The mechanisms behind foam collapse cannot be distinguished from this work alone, but plausible mechanisms are listed and discussed.…”
Section: Pv Injected Oil Recovery Fraction Of Ooip Differential Presmentioning
confidence: 85%
“…The presence of oil is of primary importance since its effect on lamellae stability depends on the extent to which the foam lamellae interact with the oil . Since foam generation and propagation in porous media is strongly oil‐specific, oil‐insensitive foams have been shown to propagate faster than oil‐sensitive foams . Earlier studies showed that alkenes with a shorter carbon chain tended to be more detrimental to foam stability, which was determined by performing a series of bulk experiments .…”
Section: Introductionmentioning
confidence: 99%
“…[16] Since foam generation and propagation in porous media is strongly MONTH 2019 THE CANADIAN JOURNAL OF CHEMICAL ENGINEERING 1 oil-specific, oil-insensitive foams have been shown to propagate faster than oil-sensitive foams. [17][18][19] Earlier studies showed that alkenes with a shorter carbon chain tended to be more detrimental to foam stability, which was determined by performing a series of bulk experiments. [8] One group of researchers stated that there is a specific critical oil saturation above which foam does not form, while others argued that high-quality foam can still be generated at relatively high residual oil saturation.…”
Section: Introductionmentioning
confidence: 99%